Effect of upright and ambulant positions versus lying down during the active first stage of labor on birth outcomes among nulliparous women: randomized controlled clinical trial - Ibrahim Heba Abdel-Fatah; Said Hanan Ibrahim Ibrahim; Elgzar Wafaa Taha Ibrahim (Sciendo, 2020)
To examine the effect of upright and ambulant positions versus lying down during the active first stage of labor on birth outcomes for nulliparous women.